Disasters in the History of Pero: Weather, Earthquakes and Epidemics in Lima during the 18th century - Carcelen Reluz, Carlos (2011)
During rhe l Sth cemury Peru was hit by a series 01' natural disasrers and cpidcmic rhat reduced borh popularion and agricultural production. Belowwe discuss th rce cases: '1he recurrent pcriod of extreme cold in che wi nrer monrhs from Augusr 1714 ro 1720 that allowed ~ major epidernic rha{ ravaged {heSourhern Andes. {he-earrhquake of 1746 in Lima, duc ro rhe magnirude of dcstrucrion and deaths markcd a rnilesrone in (he socicry and El Niño (or ENSO) from 1791 ro 1794, one of ihc rnosr darnage caused. cspccially in (he Norrh Coasr of rhe counrry